Optimizing Speckle Data Reduction for Analysis of Faint Sources - Gaulin, Joseph; Horch, E.; Howell, S.; Ciardi, D. (American Astronomical Society, AAS Meeting, 2011)
Electron-multiplying CCD cameras are now being widely used in speckle imaging, and have been shown to deliver excellent photometric precision under good observing conditions. Successful image reconstructions have been made on binary stars fainter than 14th magnitude. However, improving the speckle signal-to-noise ratio and the fidelity of image reconstructions for faint sources would be extremely helpful in several areas of research where diffraction-limited images are required, including our own ongoing speckle observations of Kepler exoplanet candidate stars using the WIYN Telescope at Kitt Peak. In this paper, we investigate (1) robust cosmic ray rejection and (2) removal of low signal-to-noise frames as two ways to maximize data quality for faint source observations. Cosmic ray rejection is not normally a major concern in speckle imaging due to the brightness of the targets traditionally observed and the short frame times. Nonetheless, when imaging faint targets, more frames are needed to achieve a given signal-to-noise ratio, increasing the chance of cosmic ray events on the detector, and even a single cosmic ray hit in the frame sequence can significantly affect the source detection ability and photometry obtained in the observation. Similarly, faint sources often exhibit some frames with a well-defined image core while in other frames it is difficult to tell if the source is even present, primarily due to seeing variation during the observation. A new speckle reduction algorithm has been created that removes cosmic rays without throwing out frames and rejects frames with bad seeing, and its performance is investigated to determine to what extent this can improve source detection and photometric reliability in the final reconstructed image. Funding for this work was provided by the Kepler Science Center and by NSF Grant AST-0908125.
Keywords: dept.phy

Speckle Imaging at Gemini and the DCT - Horch, E. P.; Löbb, J.; Howell, S. B.; van Altena, W. F.; Henry, T. J.; van Belle, G. T. (Revista Mexicana de Astronomía y Astrofísica, 2018)
A program of speckle observations at Lowell Observatory's Discovery Channel Telescope (DCT) and the Gemini North and South Telescopes will be described. It has featured the Differential Speckle Survey Instrument (DSSI), built at Southern Connecticut State University in 2008. DSSI is a dual-port system that records speckle images in two colors simultaneously and produces diffraction limited images to V∼ 16.5 mag at Gemini and V∼ 14.5 mag at the DCT. Of the several science projects that are being pursued at these telescopes, three will be highlighted here. The first is high-resolution follow-up observations for Kepler and K2 exoplanet missions, the second is a study of metal-poor spectroscopic binaries in an attempt to resolve these systems and determine their visual orbits en route to making mass determinations, and the third is a systematic survey of nearby late-type dwarfs, where the multiplicity fraction will be directly measured and compared to that of G dwarfs. The current status of these projects is discussed and some representative results are given.
Keywords: binaries: visual; dept.phy; techniques: high angular resolution; techniques: interferometric; techniques: photometric; ⛔ No DOI found

Exoplanet Characterization by Proxy for Kepler-61b: How a Nearby Star Bumped a Planet Out of the Habitable Zone - Ballard, Sarah; Charbonneau, D.; Fressin, F.; Torres, G.; Irwin, J.; Desert, J.; Ciardi, D.; Crepp, J. R.; Henze, C.; Bryson, S.; Howell, S. B.; Horch, E.; et al. (American Astronomical Society, AAS Meeting, 2013)
We present the validation and characterization of Kepler-61b: a 2.5 R_Earth planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon our identification of a spectroscopically similar star located 4.9 pc from Earth. This proxy star to Kepler-61 has a published direct interferometric radius and effective temperature measurement, which we apply in tandem with the Kepler photometry to characterize the planet Kepler-61b. The technique of identifying a nearby proxy star with directly measured properties allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had profound implications for the putative habitability of Kepler-61b. This work was performed in part under contract with the California Institute of Technology (Caltech) funded by NASA through the Sagan Fellowship Program
Keywords: dept.phy

The Relation Between Radius, Mass, and Incident Flux of Exoplanets - Weiss, Lauren M.; Marcy, G. W.; Rowe, J.; Isaacson, H. T.; Howard, A.; Fortney, J. J.; Miller, N.; Demory, B.; Fischer, D.; Adams, E. A.; Dupree, A. K.; Howell, S. B.; et al. (American Astronomical Society, AAS Meeting, 2013)
We measure the mass of a modestly irradiated giant or "warm Jupiter," KOI-94d, in order to calculate its density. We wish to determine whether this planet, which is in a 22 day orbit and receives 107 times as much incident flux as the Earth, is bloated like "hot Jupiters" or as dense as our own Jupiter. In addition to its warm Jupiter, KOI-94 hosts at least 3 smaller planets, all of which were detected through transits by the Kepler Mission. This presents the opportunity to characterize a multi-planet system and to test dynamic stability and formation theory through observations of the masses and orbital elements of these planets. With 26 radial velocity measurements of KOI-94 from the W. M. Keck Observatory/HIRES, we measure the mass of the giant planet and upper limits to the masses of the three smaller planets. Transit timing variations will allow us to hone the mass measurements of the three smaller planets. Using the KOI-94 system and all other planets with published values for both mass and radius, we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to ten Jupiter masses: log(Rp/RE) = 0.007 + 0.53 log(M/ME) - 0.001 log(F/[erg/s/cm^2]) for Mp < 150ME; log(Rp/RE) = 0.67 - 0.036 log(M/ME) + 0.06 log(F/[erg/s/cm^2]) for Mp > 150ME. We also solve these planes in density-mass-flux space: log(ρp/[g/cm^3]) = 0.69 - 0.57 log(M/ME) + 0.02 log(F/[erg/s/cm^2]) for Mp < 150ME; log(ρp/[g/cm^3]) = -1.23 + 1.10 log(M/ME) - 0.18 log(F/[erg/s/cm^2]) for Mp > 150ME.
Keywords: dept.phy

The Kepler follow-up observation program. I. a catalog of companions to Kepler stars from high-resolution imaging - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; van Belle, G. T.; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We present results from high-resolution, optical to near-IR imaging of host stars of Kepler Objects of Interest (KOIs), identified in the original Kepler field. Part of the data were obtained under the Kepler imaging follow-up observation program over six years (2009-2015). Almost 90% of stars that are hosts to planet candidates or confirmed planets were observed. We combine measurements of companions to KOI host stars from different bands to create a comprehensive catalog of projected separations, position angles, and magnitude differences for all detected companion stars (some of which may not be bound). Our compilation includes 2297 companions around 1903 primary stars. From high-resolution imaging, we find that ∼10% (∼30%) of the observed stars have at least one companion detected within 1″ (4″). The true fraction of systems with close (≲4″) companions is larger than the observed one due to the limited sensitivities of the imaging data. We derive correction factors for planet radii caused by the dilution of the transit depth: assuming that planets orbit the primary stars or the brightest companion stars, the average correction factors are 1.06 and 3.09, respectively. The true effect of transit dilution lies in between these two cases and varies with each system. Applying these factors to planet radii decreases the number of KOI planets with radii smaller than 2 R⊕ by ∼2%-23% and thus affects planet occurrence rates. This effect will also be important for the yield of small planets from future transit missions such as TESS. © 2017. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; catalogs; dept.phy; peer-reviewed; planets and satellites: detection; surveys; techniques: high angular resolution; techniques: photometric

Erratum: “The Kepler Follow-up Observation Program. I. A Catalog of Companions to Kepler Stars from High-resolution Imaging” (2017, AJ, 153, 71) - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; Belle, G. T. van; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We have added references to Tables 3 and 8 (last column in each table). Below is a sample of both tables; the full tables are available in machine-readable form.
Keywords: dept.phy

HAT-P-67b: An extremely low density Saturn transiting an F-subgiant confirmed via doppler tomography - Zhou, G.; Bakos, G. Á.; Hartman, J. D.; Latham, D. W.; Torres, G.; Bhatti, W.; Penev, K.; Buchhave, L.; Kovács, G.; Bieryla, A.; Quinn, S.; Isaacson, H.; et al. (The Astronomical Journal, 2017)
We report the discovery of HAT-P-67b, which is a hot-Saturn transiting a rapidly rotating F-subgiant. HAT-P-67b has a radius of Rp=2.085 -0.071 +0.096 RJ, and orbites a M∗ = 1.642-0.072 +0.155 M, R∗ = 2.546-0.099 +0.0084 R host star in a ∼4.81 day period orbit. We place an upper limit on the mass of the planet via radial velocity measurements to be Mp < 0.59 MJ, and a lower limit of >0.056 MJ by limitations on Roche lobe overflow. Despite being a subgiant, the host star still exhibits relatively rapid rotation, with a projected rotational velocity of v sin I∗ = 35.8 ±1.1 km s-1, which makes it difficult to precisely determine the mass of the planet using radial velocities. We validated HAT-P-67b via two Doppler tomographic detections of the planetary transit, which eliminate potential eclipsing binary blend scenarios. The Doppler tomographic observations also confirm that HAT-P-67b has an orbit that is aligned to within 12, in projection, with the spin of its host star. HAT-P-67b receives strong UV irradiation and is among one of the lowest density planets known, which makes it a good candidate for future UV transit observations in the search for an extended hydrogen exosphere. © 2017. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HAT-P-67); techniques: photometric; techniques: spectroscopic